2019
DOI: 10.2340/16501977-2559
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validity and reliability of a low-cost gait analysis system for assessment of spatiotemporal gait parameters

Abstract: Gait parameters, such as step length and step time, allow the quantification of gait deviations in persons with various diseases. Treatment can be customized and evaluated based on these parameters. However, few lowcost, easily applicable systems are available for clinical settings to accurately measure gait parameters. A lowcost spatiotemporal gait analysis system was developed and this study evaluated its accuracy and reliability. The spatiotemporal gait analysis system consists of a camera placed perpendicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
12
0
2
Order By: Relevance
“…In this study, spatiotemporal variables derived from the Kinect V2 sensor showed an excellent agreement with their referential counterparts (ICC 2,k = 0.83-0.99). In accordance with the present results, previous studies have reported a reasonable validity of the Kinect V2 when assessing spatiotemporal gait parameters regardless of what the walking condition (overground or treadmill-based), walk speed (at a self-comfortable or specific speed), population (healthy or patients with movement disorders), and also the referential motion capture system (optoelectronic cameras, videos, or press sensing mat) was [35,36,44,53,54]. This study also demonstrated good reliability of the Kinect V2 sensor for spatiotemporal measurements (ICC 2,k = 0.78-0.88), favouring prior findings [35,[55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, spatiotemporal variables derived from the Kinect V2 sensor showed an excellent agreement with their referential counterparts (ICC 2,k = 0.83-0.99). In accordance with the present results, previous studies have reported a reasonable validity of the Kinect V2 when assessing spatiotemporal gait parameters regardless of what the walking condition (overground or treadmill-based), walk speed (at a self-comfortable or specific speed), population (healthy or patients with movement disorders), and also the referential motion capture system (optoelectronic cameras, videos, or press sensing mat) was [35,36,44,53,54]. This study also demonstrated good reliability of the Kinect V2 sensor for spatiotemporal measurements (ICC 2,k = 0.78-0.88), favouring prior findings [35,[55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 92%
“…This mat consists of 18,432 pressure sensors positioned in a 348 × 48 sensor grid, producing a spatial resolution of 0.5 inches (1.27 cm), with these sensors sampled at 120 Hz. This system provides an array of spatial, temporal, and spatiotemporal kinematic variables, and has proven to be a valid and reliable measure of participants’ gait ( McDonough et al, 2001 ; Webster et al, 2005 ; Van Bloemendaal et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Step length during comfortable gait speed was measured with a customized spatiotemporal gait analysis system (SGAS). 34 Participants walked along a 10-m walkway until 5 valid left and right foot steps were collected in which each foot landed within the 130-cm-wide video field-of-view. The primary condition was walking without shoes and orthosis with as minimal as possible use of walking aids or physical assistance.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary outcomes of the efficacy study were additional spatiotemporal gait parameters (step time asymmetry index, single-leg stance time asymmetry index, stride length, and stride time) for the barefoot and shod conditions, 34-36 walking capacity measures (walking balance measured with the Functional Gait Assessment 37,38 and comfortable gait speed calculated from the 10-Meter Walk Test 37 ), and balance control measured with the Berg Balance Scale. 39 Furthermore, fear of falling was evaluated by the Falls Efficacy Scale I (score range 16-64) and assessed only at 3-month follow-up.…”
Section: Methodsmentioning
confidence: 99%